Induction, Proliferation and Differentiation of Callus in Paris polyphylla Sm. through Leaf Culture - Thapa, Chandra Bahadur; Pant, Krishna Kumar; Bhattarai, Hari Datta; Thapa, Mahendra; Pant, Bijaya (Journal of Nepal Biotechnology Association, 2024)
Paris polyphylla Sm. is a vulnerable medicinal plant employed in the treatment of various ailments. This study seeks to establish a protocol for callus induction, proliferation, and differentiation of P. polyphylla. Immature leaf explants were cultured on MS medium with varying concentrations of plant growth regulators (PGRs), including 2,4-dichlorophenoxyacetic acid (2,4-D), kinetin (Kn), 6-benzylaminopurine (BAP), Thidiazuron (TDZ), α-Naphthalene acetic acid (NAA), and Gibberellic acid (GA3), along with 10% coconut water. After 12 weeks of primary culture, the optimal callus induction was observed in MS medium supplemented with 0.25 mg/l 2,4-D + 0.5 mg/l Kn. In the secondary culture at 8 weeks, the best callus proliferation, as determined by callus weight or growth index, occurred in MS medium supplemented with 2.0 mg/l BAP alone, 2.0 mg/l Kn alone, 1.0 mg/l TDZ alone, combinations of 2.0 mg/l Kn + 1.0 mg/l BAP + 2.0 mg/l GA3, and combinations of 0.5 mg/l NAA + 2.0 mg/l BAP + 2.0 mg/l GA3, as well as 10% coconut water. Furthermore, callus differentiation into mini rhizomes with root primordia was successfully achieved in MS media containing 2.5 mg/l Kn and 10% coconut water. This study reports, for the first time, the formation and differentiation of callus from leaf explants in P. polyphylla. Large-scale callus generation from leaf explants has the potential to enhance the production of bioactive secondary metabolites for therapeutic purposes and facilitate the development of plantlets through organogenesis.